Principles of Infrastructure as Code as a Codex for Mitigating Operational Risks in Critical Services (International Journal of Engineering and Computer Science, 2025)
This article analyzes the principles of Infrastructure as Code (IaC) as a tool for reducing operational risks in critical services. Its relevance stems from the need to ensure high availability and predictability of infrastructures supporting finance, energy, and other vital sectors. The novelty lies in an interdisciplinary comparison of the latest research covering disaster recovery, DevSecOps practices, blockchain-based logging, and the use of AI agents. The study describes the main IaC styles, evaluates their contributions to lowering RTO/RPO, and examines how they establish reliable code-supply chains. Special attention is paid to the threat of widespread vulnerable configurations. The aim is to identify how IaC’s declarative model, idempotence, and automated testing decrease failure likelihood. Methods include content analysis, comparative review, and tabular synthesis. The conclusion outlines IaC’s role as a “codex” of resilience and suggests directions for further research. This work will be of value to cloud architects, cybersecurity specialists, and DevSecOps researchers.